The Development of Route Selection Application to Avoid Flood Roads (Future Science, 2021)
Street flooding is one of the problems faced by urban communities around the world, including Indonesia. The problem of street flooding is caused by various factors, including high rainfall and poor drainage. This problem certainly causes a lot of losses for road users, including vehicles becoming dirty and more severe damage. Therefore, it is necessary to choose the alternative route so that road users avoid the danger of flooding. This paper will discuss the development of applications that provide information to road users alternative routes to avoid flooded roads. An informed search algorithm called A* or A-star was employed to find the alternative paths. All flood road information, built from road users who share information through mobile applications.